A biomechanical analysis of the knee joint during power clean - Umar, Muhammad Aiman (Universiti Sains Malaysia, 2016)
To date, the biomechanical analysis of upper limb during clean and jerk event for analyzing the movement of the upper limb and reducing the risk of injury have been on-going being investigated. However, little is known about the biomechanical analysis of lower limb (knee joint) during clean and jerk event in young males and females best state-level weightlifters. This study was carried out to compare the knee joint range of motion following 1 Repitition Maximum (1-RM) and 50% of 1-RM power clean, to compare the barbell acceleration following 1-RM and 50% of 1-RM power clean at the second pull phase and to measure and analyse the knee joint reaction force during 50% of 1-RM power clean weightlifting. Twenty-five best state-level weightlifters (17 males and 8 females) volunteered to participate in this study. The biomechanical analysis was included the two-dimension (2D) kinematic analysis and three-dimension (3D) motion capture analysis. For 2D analysis test, the participants were encouraged to perform 1 Repetition Maximum (1- RM) power clean and the performances of the participants were recorded using the video camera. Meanwhile, for 3D analysis test, the power clean test at 50% of 1-RM was recorded using high speed motion capture cameras The result of this study indicated that the mean value of the knee joint range of motion (ROM) and barbell acceleration at 50% of 1-RM power clean were greater compared to at 1-RM power clean. Both parameters were statistically significant (p<0.05) between 1-RM and 50% 1-RM power clean. The knee joint reaction force (JRF) data were not comparable due to huge gap of the number of male and female weightlifters. Therefore, only the descriptive data were shown. Based on the result, the demographic data showed the overall physical evaluation of the athletes, which was in fair category. Moreover, the values of the knee joint range of motion during 50% of 1-RM and 1-RM power clean were lower than the normal range. Then, The change of the barbell acceleration was affected by the intensity of the training. Furthermore, the value of the knee joint reaction force during the second pull phase among male and female was not in the normal range. In conclusion, two-dimensional kinematic analysis was able to explore the power clean technique while the three-dimensional motion capture analysis was able to investigate the mechanical principles of power clean.